(untitled) (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to examine the effect of training and career development on employee performance at the Palopo Branch of PT Bank Rakyat Indonesia. Methodology: A quantitative research design was employed using a survey method, with data collected through structured questionnaires distributed to 80 employees. The data were analysed using descriptive and inferential statistical techniques, including Pearson product moment validity testing and reliability analysis, t-tests, F-tests, and the coefficient of determination, with the assistance of SPSS version 23. Results: The findings indicate that training has a positive and significant effect on employee performance, whereas career development does not have a significant effect. Simultaneously, training and career development have a positive and significant effect on employee performance, with an R² value of 0.156, indicating that the independent variables explain 15.6% of the variation in employee performance. Findings: The findings confirm that training is the dominant driver of performance improvement, while career development initiatives at the branch level show limited effectiveness. Novelty & Originality: This study provides novel empirical evidence on human resource development practices at a regional branch of a state-owned bank in Indonesia, highlighting contextual limitations that reduce the effectiveness of career development programmes at the branch level. Its originality emerges from the focused examination of these specific HR variables within the under-researched context of a regional banking branch. Conclusions: The results suggest that employee performance improvement can be achieved primarily through optimised training programmes, while career development initiatives require strategic evaluation to enhance their impact. Type of Paper: This paper is an empirical research paper.